PEMERTAHANAN BAHASA DAYAK SALAKO DALAM RANAH KELUARGA DESA BUKIT SEGOLER KECAMATAN TEBAS KABUPATEN SAMBAS - Desi Lestari; Laurensius Salem; Agus Syahrani (Universitas Tanjungpura, 2022)
This study aims to maintain the Salako Dayak language in the family domain in the village of Bukit Segoler. The research method used is a mixed research with a mixed form of research. The data sources of this research are speaker of the Dayak Salako language in Bukit Segoler village, Tebas sub district and the data is a questionnaire sheet answered by speaker of the Dayak Salako language and the results of the interviews with speakers of the Dayak Salako language. The result showed that the preservation of the Dayak Salako language in the village of Bukit Segoler in this study led to the patterns of maintaining the Dayak Salako language. The first pattern based on linguistic background gets a score of 80% with a total score of 1.694. the second pattern is based on thempattern of language retention based on role relationships with a score of 82% and the total score is 1.640. the third pattern is language retention according to language events with a value of 95% ang total score of 6.390. the fourth pattern is the pattern of language use according to language use with a value of 97% and the total score is 2.094.